Interacción familiar y formación de la autoestima en los estudiantes de la Unidad Educativa Juan Montalvo - Toro Leon, Jeniffer Andrea (2019)
The context in which a human evolves is not confined to a single immediate environment, but is developed to involve the interconnections between other media and the external influences that come from the most extensive situations. The family and the educational establishment are microsocieties in which the individual in advance actively participates, the relationships that exist between these two media can be as definitive for development as what happens within a specific context. The family personifies the first environment of socialization of a person and is, in turn, the bond of union between the unequal educational institutions in which it participates, containing the most important of them; the school. For its part, this establishment confronts students with culturally organized knowledge through complex and abstract concepts that transcend individual experience, however, children experience both in the formal educational environment and in the non-formal educational environment. Starting from an ecosystemic theoretical representation, the family-unit educational interactions and the importance it has in the formative process were examined, at the same time we sought to establish the commitment of parents and teachers to develop an adequate learning process within the classroom. The design of this research is qualitative, so it has a characteristic transcendence, based on a deductive-inductive method, therefore, in the process of gathering information to support this inquiry, methods such as observation and techniques were used. as the interview that will reveal significant data to consider within the proposed investigation. All this study will help to know more in depth this problem, the results obtained will facilitate the formation of appropriate self-esteem, not only to sensitize both agencies, but adopt the necessary measures that encourage family-school social interaction and strengthen the educational process